Equity of access to reproductive health services among youths in resource-limited suburban communities of Mandalay City, Myanmar - Thin Zaw Phyu Phyu; Liabsuetrakul Tippawan; Htay Thien Thien; McNeil Edward (BMC, 2012)
Abstract Background Inequity of accessibility to and utilization of reproductive health (RH) services among youths is a global concern, especially in resource-limited areas. The level of inequity also varies by cultural and socio-economic contexts. To tailor RH services to the needs of youths, relevant solutions are required. This study aimed to assess baseline information on access to and utilization of RH services and unmet needs among youths living in resource-limited, suburban communities of Mandalay City, Myanmar. Methods A community-based, cross-sectional study was conducted in all resource-limited, suburban communities of Mandalay City, Myanmar. A total of 444 randomly selected youths aged between 15 and 24 years were interviewed for three main outcomes, namely accessibility to and utilization of RH services and youth's unmet needs for these services. Factors associated with these outcomes were determined using multivariate logistic regression. Results Although geographical accessibility was high (79.3%), financial accessibility was low (19.1%) resulting in a low overall accessibility (34.5%) to RH services. Two-thirds of youths used some kind of RH services at least once in the past. Levels of unmet needs for sexual RH information, family planning, maternal care and HIV testing were 62.6%, 31.9%, 38.7% and 56.2%, respectively. Youths living in the south or south-western suburbs, having a deceased parent, never being married or never exposed to mass media were less likely to access RH services. Being a young adult, current student, working as a waste recycler, having ever experienced a sexual relationship, ever being married, ever exposed to mass media, having a high knowledge of RH services and providers or a high level of accessibility to RH services significantly increased the likelihood of utilization of those services. In addition to youths' socio-demographic characteristics, exposure to mass media, norm of peer exposure and knowledge on types of providers and services significantly influenced the unmet needs of youths towards RH services. Conclusion Despite the availability of RH services, youth's accessibility to and utilization of those services were unsatisfactory. The levels of youths' unmet RH needs were alarmingly high.